Climate in Asia and the Pacific Security, Society and Sustainability - Manton, Michael; Stevenson, Linda Anne (Advances in Global Change Research, 2014)
Commissioned by the Intergovernmental Meeting (IGM) of the Asia-Pacific Network for Global Change Research (APN), this book offers a detailed survey of the current status of climate change and climate variability in the Asia-Pacific region, a thorough and thoughtful assessment of climate and security and clear recommendations on the best paths of climate research in the future.   The opening chapter addresses current understanding of the interactions between climate, natural ecosystems and human communities across Asia and the Pacific. Chapter 2 outlines variability and change in the region, from the El Niño-Southern Oscillation (ENSO) to glaciers, tropical cyclones and extreme weather events, as well as the latest methods of measuring and collecting data and advanced techniques for creating climate models and projections. The contributors go on to unfold the many layers of this complex scientific puzzle and its political context.   Chapter 3 describes urban trends and risks and hazards from consequences of climate change, including rising temperatures and rising sea levels and highlights their effects on transportation, water supply, agriculture, food supply and energy production. Methods for adaptation and mitigation are outlined, and the contributors point out uncertainties, gaps in research and policy needs. Chapter 4 takes a broad perspective on the current and future state of agriculture and fisheries, on issues of water security from the Himalayan-Tibetan plateau to the islands of the Pacific and on energy demands and production capacity with close-up analyses of China, India and Japan. Chapter 5 examines climate and society at many levels, with special attention to remote communities in mountainous and small island settings. Chapter 6 explores sustainability, reporting on efforts to initiate and advance low carbon development, and strategies for adaptation and mitigation in natural ecosystems. The last chapter summarizes the findings presented in the book and offers a picture of future needs for climate research in the region.   As J. Scott Hauger, of the Asia Pacific Center for Security Studies writes in his foreword, this book "represents an opportunity to share knowledge and to collaborate across . . . groups and perspectives to manage the complex problems of climate related global change, to ensure a secure and sustainable environment for our children and posterity.".